The Ameliorative Effects of Isorhynchophylline on Morphine Dependence Are Mediated Through the Microbiota-Gut-Brain Axis - Chen, Zhu; Zhijie, Chen; Yuting, Zhou; Chan, Li; Shilin, Xiao; Qichun, Zhou; Jinying, Ou; Jing, Li; Chaohua, Luo; Zhixian, Mo (Frontiers in Pharmacology, 2021)
Morphine abuse is a global public health problem. Increasing evidence has shown that gut microbiota dysbiosis plays an important role in several central nervous system diseases. However, whether there is an association between gut microbiota and morphine dependence remains unclear. In this study, the effects of isorhynchophylline on morphine dependence were evaluated based on the microbiota-gut-brain axis (MGBA). The results showed that isorhynchophylline could reverse the changes in alpha and beta diversity, composition, and richness of the intestinal flora occurring in morphine-dependent zebrafish, as well as the morphine-induced changes in the expression of MGBA-related genes in BV2 cells and the brain and intestine of zebrafish. Based on the results, we then used antibiotics to evaluate whether disrupting the gut microbiota would affect morphine addiction in zebrafish. The results showed that the antibiotic-induced intestinal floral imbalance changed the behavior of morphine-dependent zebrafish, the characteristics of the zebrafish intestinal flora, and the expression of MGBA-related genes in the zebrafish brain and intestine. Importantly, we also show that, following antibiotic administration, the ameliorative effects of isorhynchophylline on morphine addiction were lost. Together, our results indicate that the gut microbiota interacts with the brain, and dysbiosis of the intestinal flora may affect the efficacy of isorhynchophylline in the body. Our findings provide a novel framework for understanding the mechanisms of morphine addiction through the MGBA and may provide new therapeutic strategies for the use of Chinese medicines in the prevention of drug addiction.